Levosimendan and Continuous Outpatient Support With Inotropes in Patients With Advanced Heart Failure: A Single-Centre Descriptive Study. Issue 4 (April 2022) - Yeung, Timothy; Dagan, Misha; Lankaputhra, Malanka; Cieslik, Luke; Warner, Victoria; Leet, Angeline; Hare, James L.; Bergin, Peter; Taylor, Andrew J.; Kaye, David M.; Patel, Hitesh C.
Abstract: To describe the use of levosimendan in a quaternary referral center with a dedicated heart failure service and compare its efficacy and safety to continuous outpatient support with inotropes (COSI) among patients with advanced heart failure (AHF) who require bridge-to-decision (BTD) or bridge-to-transplant (BTT) therapy. This study was a retrospective, single-center, descriptive study of patients with AHF who received either a single levosimendan infusion or COSI between 2018 and 2021. A total of 23 patients received a levosimendan infusion, and 14 were started on COSI. Three indications for levosimendan were identified: (1) to facilitate weaning of continuous inotropes, (2) to augment diuresis in cardiorenal syndrome, and (3) as first-line therapy for cardiogenic shock in selected patients. Eighty-three percent (19 of 23) of patients who received levosimendan survived to discharge, and there were few clinically significant adverse events. Overall survival at 12 months among patients who received levosimendan was 74%. No statistically significant difference in survival was observed at 12 months ( P = 0.68) or beyond ( P = 0.63) between patients who received levosimendan and were discharged with a plan for BTD or BTT and those who received COSI. Levosimendan is a safe and effective short-term therapy in AHF and offers comparable long-term survival to COSI in patients who require BTD or BTT therapy.